Reference intervals and 24-hour temporal stability of 82 hematological parameters, including research-use-only parameters, on the Mindray BC-780 analyser in adults from Gujarat, Western India - Dhanani, Hiren J.; Patel, Devam S.; Dhanani, Nandini H.; Sukhadiya, Mittal C.; Kothia, Jaysukh D.; Tandel, Bharat D. (International Journal of Research in Medical Sciences, 2026)
Background: The advent of advanced hematology analysers, such as the Mindray BC-780, has expanded the range of routinely reported and research-use-only (RUO) parameters, necessitating the need for accurate, population-specific reference intervals (RIs). This study aimed to define age- and gender-specific RIs for 82 parameters in a healthy adult population from Gujarat, western India, and to assess their temporal stability at room temperature (RT). Methods: A cross-sectional study was conducted involving 1,376 healthy adults aged 18-94 years. Parameters were stratified by age and gender, and RIs were established using appropriate statistical methods, following CLSI guidelines. Temporal stability was evaluated by analysing samples at baseline (immediately after collection) and after storage at RT for 4, 8, 12, and 24 hours. Results: Most parameters were non-normally distributed. Precision analysis revealed excellent reproducibility in 75 parameters. Stability testing showed 72 parameters remained stable over 24 hours at RT. Significant age- and gender-based differences were found in 47 parameters, requiring subgroup-specific reference intervals. RBC, HGB, and HCT decreased with age, while MCV and macro% increased; females showed lower RBC and HGB but higher PLT and PDW. Comparison with national and international studies demonstrated variation in a few parameters, emphasising the need for localised RIs. Conclusions: This study establishes comprehensive, population-specific RIs for routine and RUO hematology parameters and confirms the temporal stability of most parameters at RT. The findings support the adoption of region-specific RIs to enhance diagnostic accuracy and clinical decision-making.